Self-Adjointness of a Class of Multi-Spin–Boson Models with Ultraviolet Divergences - Lonigro, Davide (Mathematical Physics Analysis and Geometry, 2023)
We study a class of quantum Hamiltonian models describing a family of N two-level systems (spins) coupled with a structured boson field of positive mass, with a rotating-wave coupling mediated by form factors possibly exhibiting ultraviolet divergences. Spin–spin interactions which do not modify the total number of excitations are also included. Generalizing previous results in the single-spin case, we provide explicit expressions for the self-adjointness domain and the resolvent of these models, both of them carrying an intricate dependence on the spin–field and spin–spin coupling via a family of concatenated propagators. This construction is also shown to be stable, in the norm resolvent sense, under approximations of the form factors via normalizable ones, for example an ultraviolet cutoff.
Created from Fastlane, Scopus look-up
Keywords: Form factors; Scales of Hilbert spaces; Self-adjoint operators; Spin–boson model; Ultraviolet divergences